The Properties of Particleboard Composites Made from Pleurotus ostreatus Baglog Waste Using Citric Acid and Sucrose Adhesive (Jurnal Bahan Alam Terbarukan, 2022)
Pleurotus ostreatus (PO) is one of the edible mushrooms cultivated in baglog as the medium. Baglog’s productive age is around 4-5 weeks. The more PO produced, the amount of baglog waste also increases. The main component of baglog is wood sawdust, which contains lignocellulose; therefore, baglog has great potential to be used as a raw material for making particleboard. This research aims to make particleboard from baglog waste and determine the effect of the type and adhesive concentration on the physical and mechanical properties of the particleboard that is produced. Particleboard is made by mixing baglog waste, whose particle size is 40 mesh, with citric acid and sucrose adhesives whose concentrations are varied between 50%, 60%, and 70%. Furthermore, the particleboard was formed using a hot press machine (200 °C, 10 MPa) for 15 minutes. The obtained particleboard will be analyzed for its physical properties, including density, moisture content, water absorption, thickness swelling, morphology, and mechanical properties, including modulus of rupture (MOR) and modulus of elasticity (MOE). The test refers to the JIS A 5908-2003 type 8 standard.  As a result, particleboard made using citric acid adhesive (citric acid 70%; C70) has a better physical and mechanical properties compared to sucrose adhesive, with a density value of 0.86 g/cm³, moisture content of 4.118%, thickness expansion of 3.992%, water absorption capacity of 36.89%, 13.456%, MOR 9.682 MPa, and MOE 1.455 GPa.